Political power and vaccine neocolonialism: the exercise of word and human action - Vargas-Machado, Camilo; Cazzato-Dávila, Salvador; Vargas-Sepúlveda, Claudia (Scientific journal of social studies, 2023)
This paper analyzes the situation generated by the unequal distribution of vaccines that -internationally has occurred within the framework of the epidemic generated by COVID-19. For this, the concepts of “act” and “word” derived from the theoretical-political theses of Hannah Arendt (1993) are used, with which it was sought to demonstrate the situation of neocolonialism of vaccines derived from this situation, from philosophical deconstruction of to raise the urgent consequence of neocolonialism of health, which allowed us to infer how Human Rights are not the central axis of the discourses or of the national and state praxis of the government systems of Countries with more stable and strong economies, since the decisions and behaviors reflect the interests of the main actors of the National States that have economic support for the large-scale purchase of vaccines against COVID-19. Which in turn are the protagonists of a sociopolitical phenomenon that can be categorized as global health neocolonialism, which is presented as a phenomenon of neocolonialism that begins with the confidentiality agreements signed between the States of the countries and the pharmaceutical corporations, inside or outside COVAX in the year 2020. Concluding that the massive purchase of vaccines was subjected to an exclusivity character to acquire the lots, where some discriminatory or non-inclusion factors are revealed, stating that COVAX did not comply with the purpose for what was initially created.